Can social learning promote hybridisation? : mate-choice cpying in Drosophila subobscura populations - Silva, Gonçalo Faria, 1991- (2014)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2014